Counterclockwise modular laparoscopic anatomical mesohepatectomy using combined glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches - Zhao, Zonglei; Lyu, Xiaotong; Lyu, Xiaoqin; Kong, Lingqun; Zhao, Baolei; Zhu, Wentao; Wei, Qiang; Lin, Xutao; Cao, Xuefeng; Zhang, Xingyuan (Frontiers in Oncology, 2022)
Background Although laparoscopic anatomical hepatectomy (LAH) is widely adopted today, laparoscopic anatomic mesohepatectomy (LAMH) for patients with hepatocellular carcinoma (HCC) remains technically challenging. Methods In this study, 6 patients suffering from solitary liver tumors located in the middle lobe of the liver underwent counterclockwise modular LAMH using combined Glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches. In this process, the Glissonean pedicle approach (Takasaki approach) was first used to transect the liver pedicles of segment right anterior (G58) and segment 4 (G4). Second, the hepatic vein-guided approach was performed along the umbilical fissure vein (UFV) to sever the liver parenchyma from the caudal to cranial direction, and the middle hepatic vein (MHV) and anterior fissure vein (AFV) were then disconnected at the root. Last, the hepatic vein-guided approach was once more performed along the ventral side of the right hepatic vein (RHV) to transect the liver parenchyma from the cranial to anterior direction, and the middle lobe of the liver, including the tumor, was removed completely. The entire process was applied in a counterclockwise fashion, and the exposure or transection sequence was G58, and G4, followed by UFV, MHV, AFV, and finally, the liver parenchyma along the ventral side of RHV. Results The counterclockwise modular LAMH using combined Glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches was feasible in all 6 cases. The median duration of the operation was 275 ± 35.07 min, and the mean estimated blood loss was 283.33 ml. All of the 6 patients recovered smoothly. The Clavien-Dindo Grade I-II complications rate was up to 33.33%, mainly characterized by postoperative pain and a small amount of ascites. No Clavien-Dindo Grade III-V complications occurred, and the mean postoperative hospital stay was 6.83 ± 1.47 days. Follow-up results showed that the average disease-free survival (DFS) was 12.17 months, and the 21-months OS rate, DFS rate and tumor recurrent rate were 100%, 83.33% and 16.67% respectively. Conclusions Counterclockwise modular LAMH using combined Glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches takes the advantages of the two approaches, is a novel protocol for LAMH. It is thought to be technically feasible for patients with a centrally located solitary HCC. The oncologic feasibility of this technique needs to be investigated based on long-term follow-up. A multicenter, large-scale, more careful study is necessary.